FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS KONSUMEN PADA BISNIS E-COMMERCE (STUDI KASUS KONSUMEN TRAVELOKA PADA MAHASISWA UNIVERSITAS DIPONEGORO SEMARANG) - Putri, Rr.Dhatuswasti Hesti; Nugraha, Hari Susanta (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2017)
Improvement and development of business world would be always come together with development of existing technology. One of influenced business by internet technology is e-commerce. In the middle of tight competition between business for Traveloka, effort to create customer loyalty is an important thing to do to prevent customer from turning to another product or service.The results showed on analyze factor test is occured five variables which qualifies Measure of Sampling (MSA) to be above 0.5, that is Ease of Access (0,793), Range of Products (0,837), Price of Product (0,896), Payment Method (0,807), and Display of Product (0,842). Based on analyst, both in partial or simultant, those five variables influenced customer loyalty.The suggestion based on research, Traveloka should improve the user interface of both website and mobile application, improve the range of product especially the hotel product, put more attention on price rivalry between competitors, review the standard operating procedure of payment procedure, and improve the quality and accuracy of hotel product photo.